Development of flip pdf corporate-based e-module in learning physics of work and energy material for Class X Students of Madrasah Aliyah - Fatma Hamid; Nurhalifah Ransingin; Nurdin Abdul Rahman; Saprudin Saprudin (Institute of Computer Science (IOCS), 2023)
This research was conducted with the following objectives: 1) developing an e-module based on Flip PDF Corporate on learning physics in work and energy materials for class X students, 2) investigating the feasibility of an e-module based on Flip PDF Corporate in learning physics of work and energy material, 3) investigating teachers' responses to the Flip PDF Corporate based e-module on work and energy material produced in this research, 4) investigating students' responses to the Flip PDF Corporate-based e-module on work and energy materials produced in this study. This development research refers to the five steps of the ADDIE development design (analysis, design, development, implementation, and evaluation). The product has been validated by material experts, media experts, linguists experts. Data collection used interview guidelines, expert validation sheets, teacher response sheets and student response sheets. This research produced a product in the form of an e-module based on Flip PDF Corporate and it was very feasible to use with eligibility criteria including media experts 89%, material experts 93%, and linguists experts 97%. Teachers and students gave very good responses to the use of the e-module product developed in this study.